Comments on Mir A, Pearson S, Masood I (J Pak Med Assoc. 2023; 73: 1374-82) Where there is a will, there is a way: Enhancing contraceptive uptake in Pakistan - Nevin Adel Amer,; Amera Bekhatroh Rashed, (Journal of the Pakistan Medical Association, 2023)
Madam/sir, we have read the article, "Where there is a will, there is a way: Enhancing contraceptive uptake in Pakistan" with support and agreement on the authors view that investing in public-sector services does pay off in terms of meeting family planning needs, and so do better, wider and clearer communication. However, there are some equivocal points that require the attention and are hereby enlisted: The introduction section couldn’t give an idea about the gap of knowledge the current study tried to cover. The current study was planned to assess the contribution of a series of interventions on contraceptive uptake and reduction in unmet needs in FALAH areas at an old period of time from 2008 till 2011 while the article was published 12 years later. Being a quasi-experimental study; it was important to be conducted for testing one or more hypothesis linking the dependent and independent variables together.1 No hypothesis was formulated.